IMPLEMENTASI STRATEGI MARKETING MIX PADA PEMBIAYAAN PENSIUN BSM - Hasan, Irmayanti; Wahyuni, Adelina Dita (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Marketing strategies must be designed appropriately to meet consumer needs and achieve company goals. Marketing Mix strategy conducted by sharia banking to inform the customer about the activity in banking. The purpose of this research is to know the implementation of marketing mix strategy in BSM pension financing in PT. Bank SyariahMandiri Malang Area Office. Researchers use qualitative research with descriptive approach. The subjects of this study were three persons, data collected by observation, interview and documentation. The results showed that the implementation of marketing mix strategy at PT. Bank SyariahMandiri Malang Area Office of 7P. Product, pension financing one of its products. Price, low administrative cost and competitive margin. Promotion, by going directly to prospective customers, socialization and brochures. Place, strategic location. People, employees who play a role are Sales Force and Consumer Banking Relationship Manager. Process, there are five processes in financing. Physical evidence, PT. Bank Syariah Mandiri Malang Area Office has a fairly large and neat building.